Engajamento inteligente: um estudo de caso sobre a aplicação da neuroliderança na retenção de talentos - ALMEIDA, Ana Beatriz Rodrigues de (109, 2025)
Uma liderança efetiva é fator crucial para o engajamento dos funcionários e para direcionar seus esforços. Porém, quando inadequada, a liderança afeta negativamente o desempenho profissional, o clima e a percepção de qualidade de vida dos trabalhadores, trazendo impactos organizacionais como rotatividade e absenteísmo. Diante disso, a neurociência surge como prática importante para os líderes ajustarem suas atuações e obterem melhores resultados, merecendo ser mais bem compreendida. Nesse sentido, este estudo objetiva conhecer práticas da liderança que impactam no engajamento, bem como identificar a aplicação da neuroliderança nas empresas e seus benefícios. Para tanto, foi realizada pesquisa qualitativa de caráter exploratório baseada em pesquisa bibliográfica em material científico sobre o assunto, além de estudo de caso em uma empresa do interior paulista. Este estudo se faz importante na medida permitirá explorar um assunto recente que vem ganhando espaço no meio acadêmico e administrativo, contribuindo para a construção do conhecimento na área e para a aplicação prática nas empresas, gerando maior engajamento e consequentemente a retenção dos talentos internos. Os resultados indicam que a neuroliderança tem sido aplicada na empresa estudada por meio do desenvolvimento da empatia, feedback estruturado e gestão emocional, cujos benefícios refletem reduzindo conflitos, aumentando a motivação e melhorando a comunicação interna, fatores que são essenciais ao engajamento.

Effective leadership is a crucial factor for employee engagement and for directing their efforts. When provided, performance reaches levels of professional performance, the climate and the perception of quality of life of workers, bringing organizational impacts such as turnover and absenteeism. In view of this, neuroscience emerges as an important basis for leaders to adjust their actions and obtain better results. However, such practice seems to be unknown to most. In this sense, this objective study identifies leadership practices that impact engagement, as well as identifies the practices that companies have regarding neuroleadership and its benefits. To this end, qualitative exploratory research will be carried out based on bibliographic research in scientific material on the subject, in addition to a case study in Effective leadership is a crucial factor for employee engagement and for directing their efforts. When provided, performance reaches levels of professional performance, the climate and the perception of quality of life of workers, bringing organizational impacts such as turnover and absenteeism. In view of this, neuroscience emerges as an important basis for leaders to adjust their actions and obtain better results. However, such practice seems to be unknown to most. In this sense, this objective study identifies leadership practices that impact engagement, as well as identifies the practices that companies have regarding neuroleadership and its benefits. To this end, qualitative exploratory research will be carried out based on bibliographic research in scientific material on the subject, in addition to a case study in a company in the interior of São Paulo. This study is important as it deals with a new topic that has been gaining ground in the academic and administrative fields and can contribute to the construction of knowledge in the area and its practical application in companies, promoting greater engagement and consequently the retention of internal talent. The results indicate that neuroleadership has been applied in the company, developing empathy, structured feedback and emotional management, whose benefits reflect negative conflicts, increasing motivation and improving internal communication, essential factors for engagement.
Intelligent Engagement: A Case Study on the Application of Neuroleadership in Talent Retention
Keywords: Satisfação; Satisfação no trabalho; Liderança; Gestão e Negócios